I diritti sociali: un percorso filosofico-giuridico - CASADEI, Thomas (Strumenti per la didattica e la ricerca, 2012)
The controversial notion of social rights is situated at the heart of the relations between some key categories in the philosophical-juridical lexicon, such as equality, solidarity, citizenship and social state. The book sets out by dealing with their genesis towards the end of the eighteenth century, with particular attention to the lines of argument of Thomas Paine, to go on to examine their development, their juridical configuration and the criticisms levelled at them during the twentieth century, before arriving at basic income theories, namely alternative proposals going beyond social rights (and the juridical-constitutional forms in which they came into being). Hence, the question is dealt with up to the context of globalization and the complicated processes of European unification, also in order to single out ways to relaunch democracy itself 'from the bottom'. The underlying idea is that social rights are legitimately «fundamental» and «human rights» and that to be due they need two structural conditions: to be conceived of as «indivisible», «interdependent» and «interconnected» with respect to other fundamental rights (as ratified by the Vienna Declaration of 1993) and to be rooted contextually within a social and institutional space which today necessarily has to be multilevel but which, at the same time, does not leave aside the states' power of regulation and implementation.